Improving Junior High School Teacher Ability in Designing Higher order Thinking (HOTS) Problems - Fridgo Tasman (Fakultas MIPA Universitas Negeri Padang, 2020)
The result of 2015 PISA (Program for International Students Assessment) test which placed Indonesia in the 65th position of 72 countries showed the importance to improve the level of students thinking ability. There are many ways to improve the students’ thinking. One way to do that is by giving the students drill to solve higher order thinking problems. However, this solution is difficult to implement because designing HOTS (Higher Order Thinking Skills) problem is difficult for the teachers. Therefore, 20 junior high school mathematics teaches ware selected in order to give them training and workshop to improve their ability to design higher order thinking skills using action research methods. Three stages ware implemented in this training and workshop. First, introduction to HOTS, Second, designing HOTS Problems, and third, trying out and evaluating the test result. Product of the workshop are 30 mathematical problems in certain topic in which 15 of them are HOTS problems. To measure the effectiveness of the training and workshop, the result of pre-test and posttest were compared. Based on the data analysis, there was an increase of the ability of mathematics junior high school teachers to design problems to assess the higher order thinking skills.